The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/clen.200900125
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Characteristics of Rhodamine B from Aqueous Solution onto Baryte

Abstract: Batch sorption experiments were carried out for the adsorption of the basic dye Rhodamine B from aqueous solution using baryte as the adsorbent. The effect of adsorbent dosage, temperature, initial dye concentration and pH were studied. Adsorption data were modeled using first and second order kinetic equations and the intra particle diffusion model. Kinetic studies showed that the adsorption process followed second order rate kinetics with an average rate constant of 0.05458 g mg -1 min -1 . Dye adsorption eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 34 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…This will increase the electrostatic attraction between the adsorbent and the positively charged dyes, and thus lead to the observed increase in removal efficiency with increasing pH. However, rhodamine B has a carboxylic group [55]. At low pH, the removal efficiency increased as pH increased, which was similar to that for malachite green.…”
Section: Effect Of Phmentioning
confidence: 75%
See 2 more Smart Citations
“…This will increase the electrostatic attraction between the adsorbent and the positively charged dyes, and thus lead to the observed increase in removal efficiency with increasing pH. However, rhodamine B has a carboxylic group [55]. At low pH, the removal efficiency increased as pH increased, which was similar to that for malachite green.…”
Section: Effect Of Phmentioning
confidence: 75%
“…They are very useful in providing information about adsorption mechanisms, surface properties and affinity of an adsorbent towards an adsorbate [55].…”
Section: Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 10 000 chemically different dyes are manufactured. World dyestuff and dye intermediate production is estimated to be around 7 Â 10 8 kg per annum [1].…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, they observed that the percentage removal efficiency of RhB onto EGO decreases with increase in pH, hence EGO showed poor adsorption behavior for RhB amongst the studied cationic dyes [27]. This observation is in sharp contrast to the recent studies on the adsorption of RhB onto different anionic adsorbents [28][29][30][31]. Previous studies have shown that adsorption behavior and/or performance of GO are dictated by its method of preparation [32].…”
Section: Introductionmentioning
confidence: 82%